La escritura furiosa de Gonçalo M. Tavares - Rodríguez, Ximena; Nataloni, Silvia; Koleff, Miguel; Read, Valeria; Suárez, Maximiliano (Ferreyra Editor, 2022)
Fil: Rodríguez, Ximena. Universidad Nacional de Córdoba. Facultad de Lenguas; Argentina.